Design of multi-link rigid-flexible manipulator and analysis of finger vibration reduction - GUAN Shengqi; HAO Zhenhu; WANG Jingguo; MA Tengfei; SHI Hongyu (Xi'an Gongcheng Daxue xuebao)
Aimed at the problem that it is difficult to grasp the fragile ceramic parts stably in the sorting process, a new multi-link rigid-flexible manipulator is designed, which can effectively and stably grasp them. Firstly, based on mechanical transmission, the rigid joint and flexible material were combined to design the transmission mode of the manipulator and the optimal structure of the flexible joint, and the overall structure of the manipulator was constructed on three-dimensional software. Secondly, by simplifying the structure of the manipulator finger, the rigid-flexible coupling dynamic model of finger multi-link with tip mass was constructed by using Lagrange theory and finite element discrete method, and the dynamic equation of the manipulator finger in the motion process was solved. On this basis, the finger structure of the manipulator was optimized and improved by designing the vibration reduction scheme. The simulation results show that the vibration amplitude of the fingers of the rigid-flexible manipulator with the improved structure is reduced by 8mm and the time to restore stability is shortened by more than 4s, which improves the impact resistance in the process of sorting and grasping to a certain extent and ensures the stability in the process of grasping ceramic fragile parts.